2010
DOI: 10.1186/1471-2334-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia causes hippocampal apoptosis in experimental pneumococcal meningitis

Abstract: BackgroundBacteremia and systemic complications both play important roles in brain pathophysiological alterations and the outcome of pneumococcal meningitis. Their individual contributions to the development of brain damage, however, still remain to be defined.MethodsUsing an adult rat pneumococcal meningitis model, the impact of bacteremia accompanying meningitis on the development of hippocampal injury was studied. The study comprised of the three groups: I. Meningitis (n = 11), II. meningitis with attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
168
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(191 citation statements)
references
References 20 publications
14
168
9
Order By: Relevance
“…The neuropathologic changes in the disease model of BM show important similarities to human cases of meningitis and are characterized by focal tissue injury in the cortex, the hippocampus, and the inner ear. In the hippocampus and specifically the DG, histomorphologic analysis documented the occurrence of apoptosis scattered along the subgranular zone of the DG [14,20,44]. Similar to the in vitro results, after transplantation into rats 1 week after experimental pneumococcal infection, hippocampal cells migrated into the subgranular zone of the injured DG.…”
Section: Discussionsupporting
confidence: 64%
“…The neuropathologic changes in the disease model of BM show important similarities to human cases of meningitis and are characterized by focal tissue injury in the cortex, the hippocampus, and the inner ear. In the hippocampus and specifically the DG, histomorphologic analysis documented the occurrence of apoptosis scattered along the subgranular zone of the DG [14,20,44]. Similar to the in vitro results, after transplantation into rats 1 week after experimental pneumococcal infection, hippocampal cells migrated into the subgranular zone of the injured DG.…”
Section: Discussionsupporting
confidence: 64%
“…Recent findings with experimental animal models have suggested that neuronal damage may also be caused by pneumococcal growth outside the CNS compartment (365). Mice exposed intravascularly to purified PCW developed hippocampal apoptosis at 6 h postinoculation, an effect that was not reproduced in TLR2-or NOD2-deficient mice and was limited in mice overexpressing .…”
Section: Sepsis and Hippocampal Damagementioning
confidence: 99%
“…In Africa, the incidence was 46 per 100,000 and the CFR jumped to an alarming 67%. Half of the fatal cases of Hib meningitis worldwide (78,300) occurred in Africa (34,600). 9 In a similar survey for pneumococcal meningitis in children less than five years of age, the global incidence rate was 17 per 100,000 (38 for Africa) and the CFR was 59% (73% for Africa).…”
mentioning
confidence: 99%